Vectors $\overrightarrow{A}$ and $\overrightarrow{B}$ are shown. What is the magnitude of a vector $\overrightarrow{C}$ if $\overrightarrow{C}=\overrightarrow{A}-\overrightarrow{B}$?
$\text{A}\text{. }40\sqrt{3}$
$\text{B}\text{. }40\sqrt{2}$
$\text{C}\text{. }40$
$\text{D}\text{. 2}0$
Answer
Verified
466.8k+ views
Hint: Draw the vector $\left( -\overrightarrow{B} \right)$ and find the angle between the vectors $\overrightarrow{A}$ and $\left( -\overrightarrow{B} \right)$. The magnitude of vector $\left( -\overrightarrow{B} \right)$ is equal to the magnitude of vector $\overrightarrow{B}$. However, both the vectors are opposite directions. Then use the formula for the magnitude of the resultant of two vectors.
Formula used: $R=\sqrt{{{A}^{2}}+{{B}^{2}}+2AB\cos \theta }$
Complete step by step answer:
The vectors $\overrightarrow{A}$ and $\overrightarrow{B}$ are given. We are asked to find the magnitude of the vector $\overrightarrow{C}=\overrightarrow{A}-\overrightarrow{B}$. This vector addition can also be written as $\overrightarrow{C}=\overrightarrow{A}+\left( -\overrightarrow{B} \right)$.
Let us first draw the vector $\left( -\overrightarrow{B} \right)$. Vector $\left( -\overrightarrow{B} \right)$ is a vector whose magnitude is equal to the magnitude of vector $\overrightarrow{B}$ but its direction is opposite to the direction of $\overrightarrow{B}$ (as shown).
From the figure we get to know that the angle between the vectors $\overrightarrow{A}$ and $\left( -\overrightarrow{B} \right)$ is ${{120}^{\circ }}$.
Let us know use the formula for the magnitude of the resultant of the two vectors, i.e. $R=\sqrt{{{A}^{2}}+{{B}^{2}}+2AB\cos \theta }$ ….. (i), where are R is the magnitude of the resultant, A and B are the magnitudes of the two vectors and $\theta $ is the angle between the two vectors.
In this case, R = C, A = 40.
The magnitude of $\left( -\overrightarrow{B} \right)$ is equal to the magnitude of $\overrightarrow{B}$. Therefore, B = 40.
And $\theta ={{120}^{\circ }}$.
Substitute the values in (i).
$\Rightarrow C=\sqrt{{{40}^{2}}+{{40}^{2}}+2(40)(40)\cos {{120}^{\circ }}}$.
The value of $\cos {{120}^{\circ }}=-\dfrac{1}{2}$.
$\Rightarrow C=\sqrt{{{40}^{2}}+{{40}^{2}}+2(40)(40)\left( -\dfrac{1}{2} \right)}=\sqrt{{{40}^{2}}+{{40}^{2}}-{{40}^{2}}}=\sqrt{{{40}^{2}}}=40$.
This means that the magnitude of $\overrightarrow{C}$ is 40.
So, the correct answer is “Option C”.
Note: Alternative solution:
The magnitude of resultant of $\overrightarrow{C}=\overrightarrow{A}-\overrightarrow{B}$, is given as $C=\sqrt{{{A}^{2}}+{{B}^{2}}-2AB\cos \theta }$ ….. (1), where $\theta $ is the angle between the two vectors $\overrightarrow{A}$ and $\overrightarrow{B}$.
Therefore, A = B = 40 and $\theta ={{60}^{\circ }}$.
Substitute the values in (1).
$\Rightarrow C=\sqrt{{{40}^{2}}+{{40}^{2}}-2(40)(40)\cos {{60}^{\circ }}}=\sqrt{{{40}^{2}}+{{40}^{2}}-2(40)(40)\left( \dfrac{1}{2} \right)}=\sqrt{{{40}^{2}}+{{40}^{2}}-{{40}^{2}}}=\sqrt{{{40}^{2}}}=40$.
Formula used: $R=\sqrt{{{A}^{2}}+{{B}^{2}}+2AB\cos \theta }$
Complete step by step answer:
The vectors $\overrightarrow{A}$ and $\overrightarrow{B}$ are given. We are asked to find the magnitude of the vector $\overrightarrow{C}=\overrightarrow{A}-\overrightarrow{B}$. This vector addition can also be written as $\overrightarrow{C}=\overrightarrow{A}+\left( -\overrightarrow{B} \right)$.
Let us first draw the vector $\left( -\overrightarrow{B} \right)$. Vector $\left( -\overrightarrow{B} \right)$ is a vector whose magnitude is equal to the magnitude of vector $\overrightarrow{B}$ but its direction is opposite to the direction of $\overrightarrow{B}$ (as shown).
From the figure we get to know that the angle between the vectors $\overrightarrow{A}$ and $\left( -\overrightarrow{B} \right)$ is ${{120}^{\circ }}$.
Let us know use the formula for the magnitude of the resultant of the two vectors, i.e. $R=\sqrt{{{A}^{2}}+{{B}^{2}}+2AB\cos \theta }$ ….. (i), where are R is the magnitude of the resultant, A and B are the magnitudes of the two vectors and $\theta $ is the angle between the two vectors.
In this case, R = C, A = 40.
The magnitude of $\left( -\overrightarrow{B} \right)$ is equal to the magnitude of $\overrightarrow{B}$. Therefore, B = 40.
And $\theta ={{120}^{\circ }}$.
Substitute the values in (i).
$\Rightarrow C=\sqrt{{{40}^{2}}+{{40}^{2}}+2(40)(40)\cos {{120}^{\circ }}}$.
The value of $\cos {{120}^{\circ }}=-\dfrac{1}{2}$.
$\Rightarrow C=\sqrt{{{40}^{2}}+{{40}^{2}}+2(40)(40)\left( -\dfrac{1}{2} \right)}=\sqrt{{{40}^{2}}+{{40}^{2}}-{{40}^{2}}}=\sqrt{{{40}^{2}}}=40$.
This means that the magnitude of $\overrightarrow{C}$ is 40.
So, the correct answer is “Option C”.
Note: Alternative solution:
The magnitude of resultant of $\overrightarrow{C}=\overrightarrow{A}-\overrightarrow{B}$, is given as $C=\sqrt{{{A}^{2}}+{{B}^{2}}-2AB\cos \theta }$ ….. (1), where $\theta $ is the angle between the two vectors $\overrightarrow{A}$ and $\overrightarrow{B}$.
Therefore, A = B = 40 and $\theta ={{60}^{\circ }}$.
Substitute the values in (1).
$\Rightarrow C=\sqrt{{{40}^{2}}+{{40}^{2}}-2(40)(40)\cos {{60}^{\circ }}}=\sqrt{{{40}^{2}}+{{40}^{2}}-2(40)(40)\left( \dfrac{1}{2} \right)}=\sqrt{{{40}^{2}}+{{40}^{2}}-{{40}^{2}}}=\sqrt{{{40}^{2}}}=40$.
Recently Updated Pages
Master Class 11 English: Engaging Questions & Answers for Success
Master Class 11 Computer Science: Engaging Questions & Answers for Success
Master Class 11 Maths: Engaging Questions & Answers for Success
Master Class 11 Social Science: Engaging Questions & Answers for Success
Master Class 11 Economics: Engaging Questions & Answers for Success
Master Class 11 Business Studies: Engaging Questions & Answers for Success
Trending doubts
10 examples of friction in our daily life
What problem did Carter face when he reached the mummy class 11 english CBSE
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
State and prove Bernoullis theorem class 11 physics CBSE
The sequence of spore production in Puccinia wheat class 11 biology CBSE